A UML Frontend for IP-XACT-based IP Management - Schattkowsky, Tim; Xie, Tao; Müller, Wolfgang (Proceedings of DATE'09)
IP-XACT is a well accepted standard for the exchange of IP components at Electronic System and Register Transfer Level. Still, the creation and manipulation of these descriptions at the XML level can be time-consuming and error-prone. In this paper, we show that the UML can be consistently applied as an efficient and comprehensible frontend for IP-XACT-based IP description and integration. For this, we present an IP-XACT UML profile that enables UML-based descriptions covering the same information as a corresponding IP-XACT description. This enables the automated generation of IP-XACT component and design descriptions from respective UML models. In particular, it also allows the integration of existing IPs with UML. To illustrate our approach, we present an application example based on the IBM PowerPC Evaluation Kit.
Keywords: Unified modeling language; XML; Power system modeling; Application software; Master-slave; Power system management; Acceleration; Scattering; Software engineering; Software standards

Increased Accuracy through Noise Injection in Abstract RTOS Simulation - Zabel, Henning; Müller, Wolfgang (Proceedings of DATE'09)
Today, mobile and embedded real-time systems have to cope with the migration and allocation of multiple software tasks running on top of a real-time operating system (RTOS) residing on one or multiple system processors. Abstract RTOS simulations and timing analysis applies for fast and early estimation to configure it towards the individual needs of the application and environment. In this context, a high accuracy of the simulation compared to an instruction set simulation (ISS) is of key importance. In this paper, we investigate the accuracy of abstract RTOS simulation and compare it to ISS and the behavior of the physical system. We show that we can reach an increased accuracy of the simulation when we inject noise into the time model. Our results indicate that it is sufficient to inject uniformly distributed random time values to the RTOS real-time clock.
Keywords: Timing; Analytical models; Clocks; Performance analysis; Scheduling; Operating systems; Delay; Real time systems; Application software; Context modeling

Development of Automotive Communication Based Real-Time Systems - A Steer-by-Wire Case Study - Klobedanz, Kay; Kuznik, Christoph; Elfeky, Ahmed; Müller, Wolfgang (Proceedings of IESS09)
Safety-critical automotive systems must fulfill hard real-time constraints to guarantee their reliability and safety requirements. In the context of network-based electronics systems, high-level timing requirements have to be carefully mastered and traced throughout the whole development process. In this paper, we outline the management of scheduling-specific timing information by the application of a steer-by-wire design example. We apply the principles of the AUTOSAR-compliant Timing Augmented Description Language (TADL) following the methodology introduced by the TIMMO project[2]. Focus of the example will be the identification of end-to-end timing constraints and their refinement by means of stimuli-response event chains.
Keywords: Abstraction Level Controller Area Network High Abstraction Level Event Chain Automotive System

Integration abstrakter RTOS-Simulation in den Entwurf eingebetteter automobiler E/E-Systeme - Becker, Markus; Zabel, Henning; Müller, Wolfgang

Systematic Model-in-the-Loop Test of Embedded Control Systems - Krupp, Alexander; Müller, Wolfgang (Proceedings of IESS09)

Hardware-dependent Software for Multi- and Many-Core Embedded Systems - Doemer, R.; Gerstlauer, A.; Müller, Wolfgang (Proceedings of ASP-DAC'09)

Materielle Ressourcen – oder: Warum, wozu und wie haben und nutzen wir Güter? - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Bigga, Regine (Haushalt & Bildung)

International corporate reporting: A comparative approach, by Clare Roberts, Pauline Weetman and Paul Gordon (fourth edition) - Kosi, Urska (The International Journal of Accounting)

ON THE LONG TIME BEHAVIOR OF FREE STOCHASTIC SCHRÖDINGER EVOLUTIONS - Bassi, Angelo; Dürr, Detlef; Kolb, Martin (Reviews in Mathematical Physics)
We discuss the time evolution of the wave function which is the solution of a stochastic Schrödinger equation describing the dynamics of a free quantum particle subject to spontaneous localizations in space. We prove global existence and uniqueness of solutions. We observe that there exist three time regimes: the collapse regime, the classical regime and the diffusive regime. Concerning the latter, we assert that the general solution converges almost surely to a diffusing Gaussian wave function having a finite spread both in position as well as in momentum. This paper corrects and completes earlier works on this issue.

The importance of catalyst oxidation for the growth of carbon nanotubes on Si substrates - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Mathys, Daniel (Carbon)

Lectura Dantis: Paradiso XXVI. - Steigerwald, Jörn (Deutsches Dante-Jahrbuch)

Photonic crystal fiber with a dual-frequency addressable liquid crystal: behavior in the visible wavelength range - Lorenz, A.; Kitzerow, Heinz-Siegfried; Schwuchow, A.; Kobelke, J.; Bartelt, H. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Director Fields Around Spherical and Cylindrical Micro Particles in a Liquid Crystal Host - Matthias, H.; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

112Gb/s PolMux RZ-DQPSK with Fast Polarization Tracking Based on Interference Control - Wernz, H.; Bayer, S.; Olsson, B. E.; Camera, M.; Griesser, H.; Fuerst, C.; Koch, B.; Mirvoda, V.; Hidayat, A.; Noé, Reinhold (OFC: 2009 CONFERENCE ON OPTICAL FIBER COMMUNICATION, VOLS 1-5)

Unterhaltungsliteratur - Morrien, Rita (Metzler Lexikon DDR-Literatur. Autoren – Institutionen – Debatten)

Umwelt und Literatur - Morrien, Rita (Metzler Lexikon DDR-Literatur. Autoren – Institutionen – Debatten)

Julia Franck - Morrien, Rita (Metzler Lexikon DDR-Literatur. Autoren – Institutionen – Debatten)

Die ‚Lesbarkeit’ der (sozialistischen) Städte – Zur poetologischen Dimension der Architekturkontroversen in Brigitte Reimanns Romanfragment Franziska Linkerhand - Morrien, Rita (Literatur für Leser)

Multiplier-Free Real-Time Phase Tracking for Coherent QPSK Receivers - Hoffmann, Sebastian; Peveling, Ralf; Pfau, Timo; Adamczyk, Olaf; Eickhoff, Ralf; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

On Crack Analysis of Functionally Graded Materials with Material Forces - Mahnken, Rolf (IUTAM Symposium on Progress in the Theory and Numerics of Configurational Mechanics)

Deformation analysis for thermal shock using optical sensors and constitutive modelling - Sauerland, Kim-Henning; Mahnken, Rolf (Nondestructive Testing and Evaluation)

Mode Decomposition for Creep Simulation of Asymmetric Effects with Applications to Superalloys - Mahnken, Rolf (Key Engineering Materials)

Deformation and Damage Analysis of a Hybrid-Forming Tool under Thermal Shock Conditions - Mahnken, Rolf; Sauerland, K.-H.; Schneidt, A.; Gockel, F.-B. (PAMM)

Modellierung der Umwandlungsplastizität und Viskoplastizität niedrig legierter Stähle - Schneidt, Andreas; Mahnken, Rolf (PAMM)

Asymmetric effects of polymers in finite thermoviscoplasticity - Shaban, Ahmed; Mahnken, Rolf (PAMM)

Simulation of brittle crack growth in functionally graded materials - Mahnken, Rolf (PAMM)

Realization of Digital Coherent Receivers - Noé, Reinhold; Rueckert, Ulrich; Hoffmann, Sebastian; Pfau, Timo; Peveling, Ralf (2009 IEEE LEOS ANNUAL MEETING CONFERENCE PROCEEDINGS, VOLS 1AND 2)

Algorithms for Optical QAM Detection - Pfau, Timo; Noé, Reinhold (2009 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Multiplier-Free Realtime Phase Tracking in Digital Synchronous QPSK Receiver for Coherent Optical Detection - Hoffmann, S.; Herath, V.; El-Darawy, M.; Pfau, T.; Woerdehoff, C.; Peveling, R.; Rueckert, U.; Noé, Reinhold (2009 INTERNATIONAL CONFERENCE ON INDUSTRIAL AND INFORMATION SYSTEMS)

Towards Real-Time Implementation of Coherent Optical Communication - Pfau, T.; Peveling, R.; Herath, V.; Hoffmann, S.; Woerdehoff, C.; Adamczyk, O.; Porrmann, M.; Noé, Reinhold (OFC: 2009 CONFERENCE ON OPTICAL FIBER COMMUNICATION, VOLS 1-5)

Realtime Phase Tracking with Multiplier-Free Barycenter Approximation in Digital Synchronous QPSK Receiver for Coherent Detection - Hoffmann, S.; El-Darawy, M.; Pfau, T.; Woerdehoff, C.; Peveling, R.; Rueckert, U.; Noé, Reinhold (2009 IEEE LEOS ANNUAL MEETING CONFERENCE PROCEEDINGS, VOLS 1AND 2)

Real-time Implementation of Digital Coherent Detection - Noé, Reinhold; Rueckert, U.; Hoffmann, S.; Peveling, R.; Pfau, T.; El-Darawy, M.; Al-Bermani, A. (2009 35TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION (ECOC))

Optical time-of-flight measurement based on data transmission in a ring oscillator - Noé, Reinhold; Koch, Benjamin; Sandel, David (OPTICS EXPRESS)

Hardware-Efficient Coherent Digital Receiver Concept With Feedforward Carrier Recovery for M-QAM Constellations - Pfau, Timo; Hoffmann, Sebastian; Noé, Reinhold (JOURNAL OF LIGHTWAVE TECHNOLOGY)

38-krad/s 3.8-Grad Broadband Endless Optical Polarization Tracking Using LiNbO3 Device - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali; Hidayat, Ariya; Sandel, David (IEEE PHOTONICS TECHNOLOGY LETTERS)

9.5 Gbit/s 20 Channel 1:8 DEMUX for a Coherent Optical Receiver DSPU ASIC Input Interface - Herath, Vijitha R.; Adamczyk, Olaf; Peveling, Ralf; Woedehoff, Christian; Noé, Reinhold (2009 INTERNATIONAL CONFERENCE ON INDUSTRIAL AND INFORMATION SYSTEMS)

Hardware-Efficient Coherent Digital Receiver Concept With Feedforward Carrier Recovery for M-QAM Constellations - Pfau, Timo; Hoffmann, Sebastian; Noé, Reinhold (JOURNAL OF LIGHTWAVE TECHNOLOGY)

9.5 Gbit/s 20 Channel 1:8 DEMUX for a Coherent Optical Receiver DSPU ASIC Input Interface - Herath, Vijitha R.; Adamczyk, Olaf; Peveling, Ralf; Woedehoff, Christian; Noé, Reinhold (2009 INTERNATIONAL CONFERENCE ON INDUSTRIAL AND INFORMATION SYSTEMS)

38-krad/s 3.8-Grad Broadband Endless Optical Polarization Tracking Using LiNbO3 Device - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali; Hidayat, Ariya; Sandel, David (IEEE PHOTONICS TECHNOLOGY LETTERS)

Hardware-Efficient Coherent Digital Receiver Concept With Feedforward Carrier Recovery for $M$ -QAM Constellations - Pfau, Timo; Hoffmann, Sebastian; Noé, Reinhold (Journal of Lightwave Technology)

Analysis of an ASIC-based Coherent Polarization-Multiplexed QPSK Receiver and Different Receiver Frontends - El-Darawy, Mohamed; Herath, Vijitha; Pfau, Timo; Hoffmann, Sebastian; Peveling, Ralf; Adamczyk, Olaf; Woerdehoff, Christian; Rueckert, Ulrich; Noé, Reinhold (2009 ITG Symposium on Photonic Networks)

Algorithms for optical QAM detection - Pfau, Timo; Noé, Reinhold (2009 IEEE/LEOS Summer Topical Meeting)

9.5 Gbit/s 20 channel 1∶8 DEMUX for a coherent optical receiver DSPU ASIC input interface - Herath, Vijitha R.; Adamczyk, Olaf; Peveling, Ralf; Wödehoff, Christian; Noé, Reinhold (2009 International Conference on Industrial and Information Systems (ICIIS))

Volterra nonlinear compensation of 112 Gb/s ultra-long-haul coherent optical OFDM based on frequency-shaped decision feedback - Weidenfeld, Rakefet; Nazarathy, Moshe; Noé, Reinhold; Shpantzer, Isaac (2009 35th European Conference on Optical Communication)

Realization of digital coherent receivers - Noé, Reinhold; Rückert, Ulrich; Hoffmann, Sebastian; Pfau, Timo; Peveling, Ralf (2009 IEEE LEOS Annual Meeting Conference Proceedings)

38-krad/s 3.8-Grad Broadband Endless Optical Polarization Tracking Using LiNbO$_3$ Device - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali; Hidayat, Ariya; Sandel, David (IEEE Photonics Technology Letters)

Multiplier-Free Real-Time Phase Tracking for Coherent QPSK Receivers - Hoffmann, Sebastian; Peveling, Ralf; Pfau, Timo; Adamczyk, Olaf; Eickhoff, Ralf; Noé, Reinhold (IEEE Photonics Technology Letters)

Der hypertrophe Text als Ort des Widerstands: Rousseau und Stifter in ethischer Perspektive - Roselli, Antonio; Öhlschläger, Claudia (Narration und Ethik)

Poetik und Ethik Kleiner Prosa: Franz Kafka, Robert Musil, Heiner Müller, Michael Köhlmeier - Öhlschläger, Claudia (Zeitschrift für Deutsche Philologie)

Phosphonium Salt Organocatalysis - Werner, Thomas (Advanced Synthesis & Catalysis)
Keywords: General Chemistry